Winter wonder worlds. (December 2021) - Spring, Eleanor
Abstract : The winter holiday season comes but once a year – on Earth. Eleanor Spring takes a tour through some of the seasonal extremities experienced on distant worlds. A chilly Earth winter never looked so inviting!